The significance of restorative justice on the rehabilitation, restoration, and healing of incarcerated persons sentenced to life imprisonment: A case study of Voorberg Medium B Correctional Centre in the Western Cape - Frantz, Mariete Jolene (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.